1998
DOI: 10.1086/515294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rimantadine Treatment on Clinical Manifestations and Otologic Complications in Adults Experimentally Infected with Influenza A (H1N1) Virus

Abstract: Susceptible adults (n Å 105) were enrolled into a randomized double-blind study of rimantadine treatment of experimental influenza A infection. Subjects were cloistered for 8 days and challenged with a rimantadine-sensitive strain of influenza A H1N1 virus at the end of the first day. Fortyeight hours after challenge and for 8 days, 54 subjects received placebo and 51 received rimantadine (100 mg orally, twice a day). Symptoms, signs, and pathophysiologies were monitored. Nine subjects were not infected. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Analyses of multiple trials studying treatment of influenza with NA inhibitors concluded that lower respiratory tract complications, antibiotic use, and hospitalizations could be prevented both in healthy adults under 65 years old and in those who were 65 years or older or had chronic illnesses (29,76). Similar effects on secondary complications such as bacterial pneumonia have not been seen with the M2 inhibitors amantadine and rimantadine (36,110).…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Analyses of multiple trials studying treatment of influenza with NA inhibitors concluded that lower respiratory tract complications, antibiotic use, and hospitalizations could be prevented both in healthy adults under 65 years old and in those who were 65 years or older or had chronic illnesses (29,76). Similar effects on secondary complications such as bacterial pneumonia have not been seen with the M2 inhibitors amantadine and rimantadine (36,110).…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…1e) is 10-to 1,000-fold lower than the viral concentrations measured in the nasal turbinates and lungs of mice infected for 3-4 days with influenza (38)(39)(40)(41) and the role of these channels in controlling the amount of fluid in the respiratory tract (4,42), the present findings provide an explanation for the accumulation of fluid in the respiratory tract that is a feature of influenza infections (11,(13)(14)(15)(16). The role of epithelial Na ϩ channels in maintaining the middle ear cavities free of fluid (43,44) suggests that downregulation of Na ϩ channel activity may also underlie the known association between influenza infections and otitis media (11,45). Finally, our observation that influenza hemagglutinin inhibits Na ϩ channel activity may point the way to the development of a novel alternative to the use of Na ϩ channel blockers such as amiloride in the treatment of the Na ϩ channel overactivity seen in cystic fibrosis (46).…”
Section: ϫ2mentioning
confidence: 99%
“…They appear to shorten the duration of influenza symptoms when administered in the first 48 hours of infection, although the incidence of complications does not seem to be affected. 85 Rimantadine appears to be better tolerated and carries less central nervous system side effects 86 ; its pharmacokinetics are not altered in patients with chronic liver disease. 87 Rare adverse reactions include tremors, insomnia, dizziness, excitability, ataxia, and psychosis; gastrointestinal intolerance is more common.…”
Section: Chemoprophylaxis and Pharmacological Treatment Of Influenzamentioning
confidence: 99%